Latihan Plyometrik Intensitas Tinggi Meningkatkan Kecepatan Lari Cepat, Kekuatan Anggota Tubuh Bagian Bawah, dan Jarak Lompatan pada Atlet Pria - Jusak Syaranamual; Johny Melvin Tahapary; Mariana Ditboya Hukubun; John Rafafy Batlolona (Indonesian Journal of Physical Education and Sport Science, 2026)
Athletic performance in competitive sports is strongly influenced by explosive abilities such as initial speed, lower-limb power, and jumping ability. Although plyometric training has been widely used to improve these performance components, most previous studies have not specifically examined the effects of high-intensity plyometric training on these three performance variables simultaneously in adult male athletes. This gap in the literature represents the novelty of the present study. This study aimed to analyze the effects of high-intensity plyometric training on initial speed, lower-limb power, and jump distance in male athletes. The study employed a quasi-experimental design with a pre-test and post-test approach. The research sample consisted of 15 male athletes from the athletics unit of Universitas Pattimura who participated in a high-intensity plyometric training program for 8 weeks with a frequency of three sessions per week. The research variables included initial speed measured through a 35-meter sprint test, lower-limb power measured using the Sargent test, and jump distance measured using the standing long jump test. The data were analyzed using a paired sample t-test and one-way ANOVA with a significance level of 0.05. The results showed significant improvements in all variables after the intervention, including a 6.33% decrease in sprint time, a 25.07% increase in lower-limb power, and a 25.03% increase in jump distance, with very large effect sizes across all variables. These findings indicate that high-intensity plyometric training is effective in improving the explosive performance of male athletes. This study concludes that a high-intensity plyometric training program can serve as an effective training strategy to enhance athletes’ explosive physical abilities. Future research is recommended to employ experimental designs with control groups, larger sample sizes, and further investigation into the physiological mechanisms of neuromuscular adaptation in greater depth.